Infrared observations of saturn and Titan from Cassini - Jennings, D; Achterberg, R; Bézard, B; Bjoraker, G; Brasunas, J; Carlson, R; Coustenis, A; Flasar, F; Irwin, P; Kunde, V; Mamoutkine, A; Nixon, C; et al. (Optical Society of America, 2007)
The Composite Infrared Spectrometer (CIRS) aboard the Cassini spacecraft has been orbiting Saturn for 2-1/2 years. CIRS is a Fourier transform spectrometer that measures atmospheric thermal structure and dynamics, and atmospheric composition, of Saturn and Titan. CIRS also maps the temperatures and dynamical processes of the rings and icy moons. © 2007 Optical Society of America.